A gold nanoparticles-assisted multiplex PCR assay for simultaneous detection of Salmonella typhimurium, Listeria monocytogenes and Escherichia coli O157:H7. Issue 2 (16th December 2019) - Du, Juan; Wu, Shujing; Niu, Liyuan; Li, Junguang; Zhao, Dianbo; Bai, Yanhong
Abstract : Unfunctionalized flower-shaped AuNPs is used as colorimetric sensor for PCR product detection by naked eyes. Abstract : Foodborne pathogens are a major cause of foodborne illness, leading to a growing food safety problem in public health. This work aims to develop a novel gold nanoparticles (AuNPs)-assisted multiplex PCR assay for rapid, simple and simultaneous detection of Salmonella typhimurium ( S. typhimurium ), Listeria monocytogenes ( L. monocytogenes ) and Escherichia coli O157:H7 ( E. coli O157:H7), which are the top three foodborne pathogenic bacteria. Flower-shaped AuNPs (F-AuNPs) were used as a colorimetric sensor in this assay, based on PCR product that can help improve stability of the F-AuNPs in a certain concentration of salt solution. Detection of PCR product can be directly achieved by mixing it with F-AuNPs and NaCl, and the result is visible to the naked eye. Results showed that the optimal annealing temperature was 53.1 °C to amplify the three target pathogenic strains in multiplex PCR assay, and the optimal concentrations of the primer pairs were 0.4 μM for each of L. monocytogenes and E. coli O157:H7, and 0.2 μM for S. typhimurium . The colorimetric detection limit of PCR products by F-AuNPs was 3.125 ng μL −1, and the detection time was approximately 10 min. Simultaneous detection limit of the multiplex PCR method was 10 pg μL −1 for L. monocytogenes and S. typhimurium, and 50 pg μL −1 for E. coli O157:H7. Compared with conventional multiplex PCR assay, the F-AuNPs-assisted assay is a convenient, rapid and simple visual detection method. The excellent performance of the colorimetric sensor shows potential application in on-site detection of foodborne pathogenic strains in food samples.